A Rare Presentation of Primary Hyperparathyroidism: Generalized Brown Tumors - Zeynep Çetin (Türk Osteoporoz Dergisi)

(untitled)
Primary hyperparathyroidism is a common and easily diagnosed disease at present. However, its complicated presentation as a brown tumour is rare. Here, we present the case of a patient with knee pain and common asymmetrically located brown tumours. The parathyroid adenoma was radiologically detected, followed by successful minimally invasive parathyroidectomy. However, the brown tumours regressed after surgery. Primary hyperparathyroidism can still present with common bone involvements and can be clinically and radiologically improved with appropriate treatment.